Russian banking: The state makes a comeback? - Andrei Vernikov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2009)
The purpose of this paper is to carefully assess the size of public sector within the Russian banking industry. We identify and classify at least 78 state-influenced banks. For the state-owned banks, we distinguish between those that are majority-owned by federal executive authorities or Central Bank of Russia, by sub-federal (regional and municipal) authorities, by state-owned enterprises and banks, and by state corporations.. We estimate their combined market share to have reached 56% of total assets by July 1, 2009. Banks indirectly owned by public capital are the fastest-growing group. Concentration is increasing within the public sector of the industry, with the top five state-controlled banking groups in possession of over 49% of assets. We observe a crowding out and ero-sion of domestic private capital, whose market share is shrinking from year to year. Several of the largest state-owned banks now constitute a de facto intermediate tier at the core of the banking sys-tem. We argue that the direction of ownership change in Russian banking is different from that in CEE countries.
URN:NBN:fi:bof-201408072177
Keywords: G21; G28; P31; P43; 330; Russian banks; transition; banking; state; government; public sector; state-owned banks; state-controlled banks; state-influenced banks